2016
DOI: 10.1103/physrevfluids.1.084203
|View full text |Cite
|
Sign up to set email alerts
|

Angular velocity of a sphere in a simple shear at small Reynolds number

Abstract: We analyse the angular velocity of a small neutrally buoyant spheroid log rolling in a simple shear. When the effect of fluid inertia is negligible the angular velocity ω equals half the fluid vorticity. We compute by singular perturbation theory how weak fluid inertia reduces the angular velocity in an unbounded shear, and how this reduction depends upon the shape of the spheroid (on its aspect ratio). In addition we determine the angular velocity by direct numerical simulations. The results are in excellent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…flows such as a simple shear [24,25], and for planar flows because vorticity is orthogonal to the flow plane.…”
mentioning
confidence: 99%
“…flows such as a simple shear [24,25], and for planar flows because vorticity is orthogonal to the flow plane.…”
mentioning
confidence: 99%
“…However, we found that the two expressions are numerically equivalent for all centre-of-mass motions that we examined: sudden start (Sano 1981), linearly increasing velocity ẋ = v 0 t/t 0 , and sinusoidally varying centre-of-mass velocity ẋ = v 0 sin(ω 0 t), with coefficients v 0 , t 0 and ω 0 . It is quite common that the two methods, reciprocal theorem and asymptotic matching, yield expressions for the hydrodynamic force and torque that look different but are equivalent (Meibohm et al 2016).…”
Section: Outer Solutionmentioning
confidence: 99%
“…Following Meibohm et al. (2016), we denote the first term on the right-hand side of (3.5 a ) by . This is the well-known Stokeslet describing the far-field disturbance flow produced by an active particle in the Stokes limit.…”
Section: Matched Asymptotic Expansionsmentioning
confidence: 99%
See 2 more Smart Citations